2015
DOI: 10.1186/s12870-015-0652-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL for resistance to Mediterranean corn borer in a maize tropical line to improve temperate germplasm

Abstract: BackgroundA QTL mapping study for maize resistance to the Mediterranean corn borer (MCB) was performed with a RIL population derived from the cross B73 × CML103. To develop commercial inbreds of maize resistant to the MCB for use in Europe, it would be useful to transfer resistance from tropical germplasm like the subtropical inbred CML103 to temperate lines. The inbred B73 was chosen as representative of the Stiff Stock heterotic group, a major heterotic group used in hybrid grown in both North American and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
6
20
1
Order By: Relevance
“…The phenotypic variances associated with the QTL reported in this study were fairly low (mostly slightly below 10%). This study was in agreement with other QTL mapping studies in maize that reported low phenotypic variances on both the European corn borer, and storage insect pests (Jampatong et al, 2002;Garcia-Lara et al, 2009;Samayoa et al, 2015b;Jiménez-Galindo et al, 2017). Small phenotypic variation values may suggest that the QTL have only small effects, or have larger effects but were only more loosely linked to the marker locus Bohn et al, 2000).…”
Section: Quantitative Trait Loci For Resistance To Stem Borerssupporting
confidence: 92%
See 2 more Smart Citations
“…The phenotypic variances associated with the QTL reported in this study were fairly low (mostly slightly below 10%). This study was in agreement with other QTL mapping studies in maize that reported low phenotypic variances on both the European corn borer, and storage insect pests (Jampatong et al, 2002;Garcia-Lara et al, 2009;Samayoa et al, 2015b;Jiménez-Galindo et al, 2017). Small phenotypic variation values may suggest that the QTL have only small effects, or have larger effects but were only more loosely linked to the marker locus Bohn et al, 2000).…”
Section: Quantitative Trait Loci For Resistance To Stem Borerssupporting
confidence: 92%
“…The caution is that some QTL may not have been detected and, or, were dissimilar to those reported for related stem borers species due to the low heritability of the putative traits, and differences in trait characterization (Khairallah et al, 1998;Jiménez-Galindo et al, 2017). In a similar study, Samayoa et al (2015b) attributed such discrepancies to QTL by environment interaction effects and stressed the importance of making phenotypic evaluations in environments similar to those for which breeding materials are intended to be used.…”
Section: Quantitative Trait Loci For Resistance To Stem Borersmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, PSB-Yield-TL (RILs with the shortest tunnels among those RIL with yield above the average mean were chosen) resulted in a population that was more promising attending to the yield criteria but showed increased ear height and identical tunnel length compared to those presented by the F 2 (Table 3). Indirect changes on ear and plant height suggested that selections for an indexes in which yield is prioritized could be detrimental for resistance in the medium-long term because tunnel length made by corn borers and plant height are often tightly associated (Jímenez-Galindo et al, 2017;Ordas et al, 2010;Schon et al, 1993;Samayoa et al, 2015;Samayoa et al, 2014). Similarly, in previous studies, indirect effects on plant and ear heights have been observed when selection for increased resistance has been performed (Sandoya et al, 2010;Butron et al, 2012).…”
Section: Annals Of Applied Biologymentioning
confidence: 90%
“…These results validated the positions and effects of QTL for tunnel length detected by Ordás et al (Ordas et al, 2010) and encourage us to persevere in using marker-assisted selectionMAS approaches for simultaneous improvement of yield and resistance to stem borer attack; a task rarely accomplished using conventional breeding tools (Butron et al, 2014;Bohn et al, 2003). However, as resistance to stem tunneling by MCB has been proved to be highly polygenic, based on many genes with small effects that could get undercover in QTL studies, more promising results are expected to be attained if marker-assisted selectionMAS is rather based on genome-wide than on QTL approaches (Foiada et al, 2015;Ordas et al, 2009;Ordas et al, 2010;Samayoa et al, 2015;Samayoa et al, 2014;Jímenez-Galindo et al, 2017).…”
Section: Annals Of Applied Biologymentioning
confidence: 99%